Tormentillae rhizoma – Review for an Underestimated European Herbal Drug - Melzig, Matthias F.; Böttger, Stefan (Planta Medica, 2020)
Potentilla erecta is a medicinal plant described under its traditional name Tormentil in medieval herbal books and used until today in many European countries. Today monographs for Tormentillae rhizoma in the European pharmacopeia, as well as a monograph of the Herbal Medicinal Product Commission as a drug for traditional use, exist. The present review summarizes published investigations in phytochemistry and pharmacology, together with new findings reflecting the mechanisms of action of ellagitannins as one of the main ingredients of this herbal drug. Taken together all in vitro and in vivo investigations’ data support the traditional use for treatment of diarrhea and mucosal inflammation despite a lack of suffcient clinical studies.
Keywords: Potentilla erecta; Tormentil; Rosaceae; phytochemistry; pharmacology; traditional use